Digital campaign implementation through tiktok as a strategy to increase brand awareness on the @radiokardopa.kdigi Account - Bunayyati Hakimah Sembiring Meliala; Muhammad Yafiz; Nurbaiti Nurbaiti (Institute of Computer Science (IOCS), 2023)
This study aims to find out how companies implement digital campaign strategies to increase brand awareness. The research method used by the author in this article is qualitative with a descriptive case study approach that takes the Tiktok account @radiokardopa.kdigi as the object of research. This research was conducted to provide an overview and explanation of a feature of a phenomenon studied. In this article, the phenomenon that occurs is the changing times that make Kardopa 99.4 FM Radio have to follow the trend that continues to grow in order to increase the company's brand awareness through Tiktok as a subject and marketing medium. The implementation that can be used in this strategy is as follows; Interesting and creative content is the key to getting the Tiktok audience's attention, Using relevant hashtags can help content to be found more easily by an audience interested in the topic, and interaction with users is also very important to build a good relationship between the company and the audience. Based on research results, this company is able to increase brand awareness in implementing digital campaign strategies. To find out this, researchers used total engagement data. The results of the data from January to June are; January gained 0.6%, then February 7.54%, April 21%, May 25% and June 28%. Researchers used total engagement data.